2018
DOI: 10.1176/appi.ps.201700346
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Utilization of Acute Care Services for Lithium Toxicity

Abstract: Newly initiated, potentially interacting medications are a major preventable driver of ACS use for lithium toxicity, whereas age, chronic disease, and total daily lithium dose are small but significant factors. Clinicians should use extra caution when initiating a potentially interacting medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…8 A recently published US analysis found the prevalence rate of lithium toxicity was 2.2%. 9 Results from both groups show that drug interactions were an important cause of increased lithium levels, and specifically that initiating a medication that could interact with lithium was associated with 30-fold higher risk of needing acute care for lithium toxicity. 9 Possible drug interactions include nonsteroidal anti-inflammatory drugs, diuretics, and renin-angiotensin-aldosterone system inhibitors.…”
Section: How Lithium Workmentioning
confidence: 98%
See 3 more Smart Citations
“…8 A recently published US analysis found the prevalence rate of lithium toxicity was 2.2%. 9 Results from both groups show that drug interactions were an important cause of increased lithium levels, and specifically that initiating a medication that could interact with lithium was associated with 30-fold higher risk of needing acute care for lithium toxicity. 9 Possible drug interactions include nonsteroidal anti-inflammatory drugs, diuretics, and renin-angiotensin-aldosterone system inhibitors.…”
Section: How Lithium Workmentioning
confidence: 98%
“…9 Results from both groups show that drug interactions were an important cause of increased lithium levels, and specifically that initiating a medication that could interact with lithium was associated with 30-fold higher risk of needing acute care for lithium toxicity. 9 Possible drug interactions include nonsteroidal anti-inflammatory drugs, diuretics, and renin-angiotensin-aldosterone system inhibitors. 9 Because lithium is eliminated exclusively by the kidneys, impaired or altered renal function can increase the risk of lithium retention, leading to intoxication.…”
Section: How Lithium Workmentioning
confidence: 98%
See 2 more Smart Citations
“…There are few population-based studies reporting on rates of lithium toxicity. A case–control study identified a prevalence rate of 2% for lithium toxicity over a 5-year study period (Heath 2018), whereas a large Swedish population-based study identified a rate of 7% over a 17-year period (Ott 2016). Lithium intoxication is a common occurrence over several years of treatment but annual incidence remains low, with an incidence rate of 1/100 lithium-treated patients developing intoxication per year of lithium treatment in the Swedish observational study (Ott 2016).…”
Section: Epidemiologymentioning
confidence: 99%